The doctrine of the margin of appreciation as a tool of relativisation of freedom of religion. : Some reflections on the jurisprudence of the European Court of Human Rights - Jakuszewicz, Adam (Studia Prawnoustrojowe, 2021)
The objective of the paper is to determine the implications for the interpretation of Article 9 of the European Convention on Human Rights resulting from the Court’s affording to national authorities the wide margin of appreciation when deciding whether in a given case there is a need to limit the exercise of freedom of religion. The use of the doctrine of margin of appreciation in such cases is justified both by the lack of an all-European consensus as to the proper model of relations between the state and religious communities and by divergences of views and traditions concerning the importance and impact of religion in the society. In consequence, the Court holds that restrictions on freedom of religion on grounds of the principle of secularism, which in some countries has a rank of a constitutional principle of the political system, are compatible with the Convention. This is the case eve where establishing a link between the restriction of this kind with any of the legitimate aims outlined in Article 9.2 of the Convention is highly disputable, if not impossible. Moreover, the excessive use of the doctrine of margin of appreciation in this context makes the protection level of freedom of religion contingent on prevailing ( not always rational and free from prejudice )views and attitudes towards some forms of manifestation of religious beliefs. This outcome, however, is difficult to reconcile with values underlying the Convention and the need for minority protection